The Effectiveness of Educational Video Media About Menstrual Hygiene on Adolescent Girls' Attitudes (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
Women of all ages can experience reproductive health issues. Adolescent girls often lack education about the importance of maintaining personal hygiene during menstruation, which can negatively impact their reproductive health. Therefore, this study will test the effectiveness of educational videos about menstrual personal hygiene on the attitudes of adolescent girls at the Sekupang Qur'an Center in Batam City in 2023. This study used a quasi-experimental method involving 37 adolescent girls who underwent a pre-test and a post-test. The results showed that before the intervention, the majority of respondents (70.3%) had negative attitudes regarding menstrual personal hygiene. After the intervention, the majority of respondents (83.8%) had positive attitudes. Data analysis showed that educational videos were effective in improving adolescent girls' attitudes about menstrual personal hygiene, with a p-value of 0.001 < 0.05. The results concluded that the use of educational videos was effective in improving adolescent girls' attitudes about menstrual personal hygiene. Health education through this media can be an effective tool in increasing awareness among adolescent girls regarding their reproductive health. This research has important implications for improving the reproductive health of adolescent girls and reducing the risk of infections and reproductive disorders in the future.